Plants: past and present in the battle against diabetes (Journal of Medical Science, 2023)
From ancient times, when medicine was based on folk knowledge, to the present era of advanced science, the beneficial effects of plants on various diseases, including diabetes, have been discovered. Approximately 537 million people worldwide have diabetes, and forecasts indicate further increases. Hence, there is a need to develop new effective therapies and interventions to support diabetes treatment. Many plants impact carbohydrate metabolism, and the amount of in vitro and in vivo research on animals and humans continues to grow, updating our knowledge about their potential applications in diabetes treatment and its complications. This review discusses six plant sources with proven anti-diabetic activity. The study serves as a literature review on plants and their derived compounds that exhibit hypoglycemic effects, which are significant in managing prediabetic conditions and diagnosed diabetes.